Material thoughts - Bramston, Dave, ....- (Lausanne : AVA Academia, 2009)
Basics Product Design: Material Thoughtsdescribes the various materials and processes available to product designers, and how to use and combine them. It encourages an experimental approach to product design and finishing. The book explores the thinking of leading designers and producers who challenge convention through curiosity and experimentation. It aims to promote a physical enquiry of materials and a mentality that is constantly asking ‘what could be done if…?' Key contributors include: Alessi, Chris Kabel, Demakersvandroog, Drummond Masterton, Ettore Sottsass, Front, Gene Kiegel, Industreal, Inflate, Ingo Maurer, Jaime Hayon, Jurgen Bey, Kartell, Maarten Baas, Mathias Bengtsson, Matthias Pliessnig, Memphis, molo, Philippe Starck, Shigeru Ban, Simon Heijdens, Stuart Haygarth, Stuart Walker, Studio Libertiny, Tejo Remy and Rene Veenhuizen.
Includes bibliographical references.
Keywords: Materials; New products -- Design